Daily mortality and environment in English conurbations. Air pollution, low temperature, and influenza in Greater London. Issue 1 (March 1977) - Macfarlane, A
Abstract : With the decline in concentrations of suspended particulate pollution in Greater London the association seen in the 1950s and early 1960s between daily mortality and air pollution in the conurbation is no longer apparent. Associations between unusually cold weather and short-term increases in mortality have been noted; there appears to be a tendency for influenza epidemics to follow cold spells.